Interlaboratory variability in the measurement of direct oral anticoagulants: results from the external quality assessment scheme. (29th January 2018) - Tripodi, A.; Chantarangkul, V.; Legnani, C.; Testa, S.; Tosetto, A.
Abstract : Essentials Tests for direct oral anticoagulants (DOACs) are not widely applied. These tests are perceived to be difficult to run and subjected to large between‐lab variation. We carried out proficiency testing surveys for DOAC testing in Italy. Interlab variability was small and similar to that of the international normalised ratio. Summary: Background: Tests for direct oral anticoagulants (DOACs) are not widely available. The perception that they are difficult to perform and are subject to large between‐laboratory variation makes their implementation difficult. Aims: We carried out proficiency‐testing surveys for DOACs within the activity of the external quality‐assessment scheme of the Italian Federation of Thrombosis Centers. Design: Participants were provided with coded freeze‐dried plasmas without or with graded concentrations of the three main DOACs, and asked to measure prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time and DOAC concentrations with dedicated tests. The results were centralized for statistical analysis. Results and conclusions: All participants ( n = 235) reported results for PT and APTT, and approximately one‐third reported results for DOAC concentration. PT and APTT showed variable responsiveness to DOACs: PT was more responsive to rivaroxaban than to dabigatran or apixaban. APTT was more responsive to dabigatran than to rivaroxaban or apixaban. The thrombin time ratio (test/normal) was close to unity for plasmas without dabigatran, and was high (i.e. 7.6‐fold or 15.4‐fold longer than the plasma free from the drug) for plasmas containing dabigatran at low (i.e. 42 ng mL −1 ) or high (i.e. 182 ng mL −1 ) concentration. Dedicated tests were responsive to the respective drugs, and their interlaboratory variability was relatively small (overall coefficients of variation of 8.7%, 8.4% or 10.3% for dabigatran, rivaroxaban and apixaban, respectively) and was comparable to that observed within the same survey for the International Normalized Ratio (i.e. 11.4%). In conclusion, tests for DOAC measurement performed reasonably well in a national quality‐control scheme. Regulatory authorities should urgently issue recommendations on their use, and clinical laboratories should make them available.